Free convection in a shallow wavy enclosure - Varol, Yasin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2006)
This paper presents the simulation of free convection heat transfer and fluid flow in a horizontal and shallow wavy enclosure. Its bottom wall is varied with a sinusoidal function while the top wall is flat. The wavy wall has constant hot temperature and ceiling is cold as verticals are insulated. The simulations are performed using CFDRC software. Results are presented in terms of streamlines, isotherms and Nusselt number for different aspect ratios, non-dimensional wave length and Rayleigh number. The obtained results showed that heat transfer is increased with the decreasing non-dimensional wave length and it is increased with the increasing of aspect ratio and Rayleigh number. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: natural convection; wavy enclosure; heat transfer